The power of argumentation - Suárez Iñiguez, E. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2007)
This book is a collection of essays on the philosophy of Karl Popper written by some outstanding contributors from all the world around. Most of them are Popperians, some were Sir Karl's students in his famous seminar at the London School of Economics and his research assistants. All have written books or papers on Popper's philosophy and are notable professors at their universities. So, from a well-acquainted view of Poppers philosophy the book deals with present day philosophical problems and offers interesting interpretations. The first part is devoted to political philosophy and the second to philosophy of science. The volume is of interest for all those concerned not only in Popper's philosophy but also in some the main scientific and political problems of today.